Preparation and physicochemical properties of mwcnt doped polyvinyl chloride / poly (?-caprolactone) blend - Pekdemir, Mustafa Ersin; Kok, Mediha; Qader, Ibrahim Nazem; Aydogdu, Yildirim (Springer, 2022)
In this study, a poly epsilon-caprolactone / polyvinyl chloride, PCL: PVC, (1:1) blend was composited with different concentrations of multiwalled carbon nanotube (MWCNT). The effect of the various compositions of MWCNT on the blend was investigated by Attenuated Total Reflectance Infrared Spectroscopy (ATR-IR), Differential scanning calorimetry (DSC), Thermogravimetric Analysis (TGA), and Scanning Electron Microscope (SEM). Also, the mechanical test was explored using the tensile test. Additionally, one of the composites was trained to study shape memory properties. The results showed that the composites can return their original form, therefore neither PCL nor MWCNT had any side effect on the shape memory properties of the PCL. The mechanical properties of the composites have been significantly influenced by adding MWCNT to the blend. The ultimate stress, resilience, and modulus of the toughness of the composite diminished with increasing MWCNT, however, the fracture point and ductility were comparably improved. Furthermore, the addition of MWCNT to the blend increased the melting temperature and improved the thermal stability of the composite.
Keywords: MWCNT; PCL; Blend; Nanocomposite; Crystallinity